THE INCREASE IN LEARNING OUTCOMES OF ELEMENTARY SCHOOL MATHEMATICS THROUGH PROBLEM-BASED LEARNING - Robayani, Ririn; Irawan, Edy Bambang; Atweh, Bill (Journal of K6, Education and Management, 2018)
The aims of the research is to improve learning outcomes of mathematics through problem-based learning. Classroom action research applied which was conducted in two cycles. Results showed that problem-based learning could improve learning outcomes of elementary school mathematics. The implementation of learning was performed well that can be seen from the results of cycle I and cycle II which has already achieved the predetermined criteria.